STUDI KASUS SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT PERNAPASAN - Christ Bastian Waruwu; Chairisni Lubis; Agus Budi Dharmawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
In coping with a disease usually go to the doctor or to a health clinic to get the healing, especially respiratory diseases. Because so many respiratory diseases and symptoms, so an expert or a doctor needs to examine more deeply the symptoms experienced by patients to be able determine the illness. Therefore made respiratory expert system using Dempster Shafer and Naïve Bayes Classifier. In the research, the results of testing both methods are respectively 90% in Dempster-Shafer method and 94,28% in Naïve Bayes Classifier method.